Studies on Latin American freshwater macroinvertebrates: recent advances and future directions - Ramírez, Alonso (2014)
Latin America is an active scientific research area, in particular with respect to the study of freshwater macroinvertebrates. The present serves as an introduction to a special issue that highlights recent research projects on macroinvertebrates in Latin America. As part of this introduction, we conducted a literature analysis of the last 14 years of publications from the region that highlights the steady increase in publications on macroinvertebrates. Most studies from 2000-2013 were conducted in Brazil, Colombia, Argentina, and Costa Rica, and were focused on taxonomy and different issues related to biodiversity and distribution. There was a tendency for the use of local low-impact journals, but high impact publications were also found. This special issue contributes with 18 studies conducted in eight different countries. Two major topics are covered in the special issue, the ecology and natural history of aquatic macroinvertebrates and their use in the evaluation of anthropogenic impacts to aquatic ecosystems. Based on the literature review and contributions included in the issue, we discuss research needs for the region. Identified needs include: (1) to continue emphasizing taxonomic research, (2) assess mechanisms responsible for changes in biodiversity, (3) assess the role of macroinvertebrates in ecosystem processes and function, (4) improve biomonitoring efforts beyond unimetric indices, (5) the need for an ecosystem perspective, and (6) establishing long-term studies. This special issue is an initial effort to advance our knowledge on freshwater macroinvertebrates in Latin America. Rev. Biol. Trop. 62 (Suppl. 2): 9-20. Epub 2014 April 01.